Epidemiology of UK neonatal infections: the neonIN infection surveillance network. Issue 6 (5th December 2017) - Cailes, Benjamin; Kortsalioudaki, Christina; Buttery, Jim; Pattnayak, Santosh; Greenough, Anne; Matthes, Jean; Bedford Russell, Alison; Kennea, Nigel; Heath, Paul T
Abstract : Objective: To describe the epidemiology of neonatal infection over the past decade in UK neonatal units. Design: Retrospective analysis of prospectively collected infection surveillance network data from 2005 to 2014. Setting: 30 neonatal units in the UK. Patients: Newborns on participating neonatal units who had a positive blood, cerebrospinal fluid or urine culture and were treated with at least 5 days of appropriate antibiotics. Results: 2171 episodes of neonatal infection in 1922 infants were recorded. The incidence of infection was 6.1/1000 live births and 48.8/1000 neonatal admissions (2.9 and 23.5 respectively if coagulase-negative staphylococci (CoNS) cultures excluded). The incidence of infection showed a statistically significant reduction over time with reductions in the rates of both early-onset sepsis (EOS) and late-onset sepsis (LOS). The majority of episodes (76%) represented LOS (diagnosed > 48 hours after birth), and infection was more common in premature (<37 weeks gestation) and low birth weight (<2500 g) neonates (84% and 81%, respectively). Commonly identified pathogens included group B streptococci (43%) and Escherichia coli (18%) for EOS, while E. coli (15%), Staphylococcus aureus (14%) and CoNS were prominent causes of LOS. Conclusions: This paper describes the epidemiology of neonatal infection in the UK over the past decade. These data enable benchmarking of practice and inform areas of future research and guideline development. The results support the hypothesis that the introduction of infection prevention care bundles and antibiotic stewardship programmes in the UK has reduced the burden of LOS.